(3TQM TQGFY GdESdGes - (3eLghds ((3eMSf Hf LHQ Hf YHO GddWja GdYHhOjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3cJGH GdUdGI ; GdUdGI dZI GdOYGA bGd Gddg JYGdi (B{ (3hUqd Ydjge (B} (3hbGd GdfHj U hUdJ Ydjce GdedGFcI hEPG Ccd YfO GdUGFe UdJ Ydjg GdedGFcI hHYV Cgd GddZI (B...s
(3BNQgG (B:s
... (3haj fjI GdbVGA hGdCOGA ahdGf hgd HJYOO GdSHH YfO JNdd GdSLhO (B.. (3fYe dbjGe GdSHH hCUGdI YOe GdJOGNd hgh JYdjd VYja Ke fbd QhGjI eMeO Hf eSde GdSGHbI hgj ZjQ OGdI Ydi eOYGg (B. (3bO Je GdeKUO GdChd ef cJGH GdUdGIs
(3cJHg dTjNg MSjf Hf Ydj Hf UGOb GdHMQGfjs
(3JHUQI GdYfhGf (B:s
(3TQGFY GdESdGe ddeMbb GdMdjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis